EARLY STRENGTH TESTING AFTER ACL RECONSTRUCTION IMPACTS ISOKINETIC STRENGTH PERFORMANCE AT TIME OF RETURN TO SPORT. Issue 7 (30th July 2021) - Weaver, Adam; Roman, Dylan; Mosha, Maua; Giampetruzzi, Nicholas
Background: The standard of care in ACL reconstruction (ACLR) typically involves standardized strength testing at 6 months or later to assess a patient's readiness to return to play (RTP) using isokinetic and isometric testing, and functional strength testing. Recent literature suggests that isokinetic knee extension strength should demonstrate 89% limb symmetry index (LSI) or greater prior to returning to sport. However, there is little known on the effects of strength testing early in the rehabilitation process and the relationship to strength test performance at time of RTP. Purpose: The purpose of this study was to examine how early post-operative strength test performance impacts isokinetic strength outcomes at RTP testing in adolescents. Methods: The retrospective cohort study included patients undergoing primary ACLR between 12 and 18 years of age, early post-operative strength measures, and isokinetic dynamometer strength at RTP from July 2017 and April 2019. Data was dichotomized into desired outcomes at 3 months: >70% isometric knee extension LSI, > 20 repetitions on anterior stepdown test (AST), > 90% LSI Y Balance. At RTP testing, isokinetic knee extension strength data was categorized into >89% LSI at 3 speeds (300, 180, 60°/sec). Chi square testing and odds ratio statistics were used to examine association and its magnitude. Results: 63 patients met inclusion criteria (38 females; 15.37±1.66 years old). >70% LSI isometric knee extension strength at 3 months showed a significant association (Table 2) and demonstrated the strongest odds of having >89% LSI on isokinetic strength tests at all 3 speeds at RTP with 180°/sec being the highest (OR=14.5; 95% CI=4.25, 49.43; p= <0.001). Performance on AST showed a significant association (χ2 (1, n=63) = 17.00, p <0.001), and highest odds at 180°/sec (OR=4.61; 95% CI = 1.59, 13.39, p=<0.001) and 60°/sec (OR= 3.07; 95% CI = 1.10, 8.63, p= 0.04). Combination of performance on isometric strength tests and AST showed a significant association to isokinetic strength at all three speeds, but less predictive then isometrics in isolation. (Table 2). There was no significant relationship between YBR LSI at 3 months and isokinetic strength at 6 months. Conclusion: Standardized strength testing early in rehabilitation can help identify patients that will successfully complete RTP testing. Our results suggest that isometric knee extension strength and timed anterior stepdown test provide meaningful clinical information early in the rehabilitation process. This data also suggests that the use of YBAL for predicting isokinetic strength performance is limited. :